Integrating Critical Discourse Analysis on Sustainable Tourism in English Language Learning in University - Ayomi, Putu Nur; Maharani, Putu Devi; Tustiawati, Ida Ayu Mela (Lingua Cultura, 2023)
The research discussed that discourses on tourism in social media often contradict the perspective of sustainable tourism. In engaging with public texts, students must develop a critical mindset to be able to filter information as well as to contribute their constructive ideas in solving problems in society. This could be developed as students learn some language skills in EFL, especially writing. The research applied a qualitative descriptive approach that focused on observing techniques, processes, and learning outcomes of writing skills by implementing Critical Discourse Analysis (CDA). The research used the participant observation method, where the researcher participated in the activities carried out by the group under study. The research population was students taking the English for Journalism course. The research sourced its textual material from selected online news articles and social media posts. The research involved several steps: student selection, questionnaire design and distribution, CDA and Sustainable Tourism training, feature article writing, writing assessment, and developing CDA integration models in learning. The findings show the positive impact of integrating CDA into writing instruction, notably by introducing the perspective of sustainable tourism. Students demonstrate enhanced critical writing abilities, enabling them to respond and contribute to more informed and thoughtful discussions surrounding tourism and sustainability to the content encountered on the internet that often contradicts the perspective of sustainable tourism. In engaging with public texts, students must develop a critical mindset to be able to filter information as well as to contribute their constructive ideas in solving problems in society.